2020
DOI: 10.1038/s41522-020-0122-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporospatial shifts in the human gut microbiome and metabolome after gastric bypass surgery

Abstract: Although the etiology of obesity is not well-understood, genetic, environmental, and microbiome elements are recognized as contributors to this rising pandemic. It is well documented that Roux-en-Y gastric bypass (RYGB) surgery drastically alters the fecal microbiome, but data are sparse on temporal and spatial microbiome and metabolome changes, especially in human populations. We characterized the structure and function (through metabolites) of the microbial communities in the gut lumen and structure of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 71 publications
3
63
0
5
Order By: Relevance
“…In recent years, microbiome studies using multi-omics approaches have greatly deepened our understanding of the relationship between microbiomes and hosts. For example, multi-omics studies of the gut microbiome and the human metabolome ( Chen M. X. et al, 2019 ; Ilhan et al, 2020 ) have provided new understanding in human health and diseases. In order to help the application of multi-omics technologies on plant metabolome and microbiome studies, we reviewed the data integration and analysis methods for studying human and animal microbiomes and metabolomes; and provided a few suggestions on how they could be used for plant studies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microbiome studies using multi-omics approaches have greatly deepened our understanding of the relationship between microbiomes and hosts. For example, multi-omics studies of the gut microbiome and the human metabolome ( Chen M. X. et al, 2019 ; Ilhan et al, 2020 ) have provided new understanding in human health and diseases. In order to help the application of multi-omics technologies on plant metabolome and microbiome studies, we reviewed the data integration and analysis methods for studying human and animal microbiomes and metabolomes; and provided a few suggestions on how they could be used for plant studies.…”
Section: Introductionmentioning
confidence: 99%
“…The vials were then cooled and measured for COD concentration in mgCOD/L using a spectrophotometer (HACH DR2800 Laboratory Spectrophotometer). For microbiome composition analysis, we performed 16S rRNA gene amplicon sequencing using Illumina sequencing technology and found core differences as described [ 24 , 25 ]. Further detailing regarding the 16S rRNA amplicon sequences is presented in Supplementary File S5 .…”
Section: Methodsmentioning
confidence: 99%
“…Increased prevalence of Roseburia (88) and Akkermansia were reported in association with medical weight loss (89). Although transient changes were observed at 3 months after medical weight loss, the gut microbiota composition had a tendency to return to baseline composition after 1 year (81) Firmicutes (78) Fusobacteria (73,75) Bifidobacteriaceae (73) Proteobacteria (73,75,78) Anaerostipes (78) Akkermansia (79,80) Bacteroides (79) Alistipes (97) Bifidobacterium (73,97) Bacteroides (97) Blautia (76,80,97) Citrobacter (78,80) Faecalibacterium (78,98) Fusobacterium (73) Coprococcus comes (78) Granulicatella (73,80) Faecalibacterium prausnitzii (75,78) Klebsiella (79,80) Streptococcus salivarius (98) Streptococcus (76,79,80,98) Veillonella (73,76,78,80) Alistipes shahii (75,79) Streptococcus parasanguinis (75,79) Streptococcus salivarius (75) Streptococcus thermophiles (75,79) Veillonella dispar (75,78) Veillonella parvula (75,78) SG Bacteroidetes (81) Firmicutes (74) Fusobacteria (74) Bifidobacteriaceae (73,74) Akkermansia (73,…”
Section: Microbiomes and Bariatric Surgerymentioning
confidence: 99%
“…A possible link between gut microbiota alterations and improved asthma symptoms includes increased production of SCFAs, particularly butyrate and propionate. Following RYGB, increases of propionate/acetate and butyrate/acetate ratios were reported in humans (72,80), although another study reported a postsurgical tendency of SCFAs to decrease after RYGB (84). Although SCFAs have a conflicting role in obesity, butyrate (50,52) and propionate (49,50,52,54) were associated with reduced proinflammatory cytokines and/or increased immunosuppressive cytokines, which could, in turn, modulate the pathobiology of asthma concurrent with obesity.…”
Section: Bariatric Surgery Microbiome Alterations and Asthma Concurmentioning
confidence: 99%
See 1 more Smart Citation